An open world : how America can win the contest for twenty-first-century order - Lissner, Rebecca; Rapp-Hooper, Mira (Yale University Press, 2020)
"This ambitious and incisive book presents a new vision for American foreign policy and international order at a time of historic upheaval. The United States global leadership crisis is not a passing shock created by the Trump presidency or COVID-19, but the product of forces that will endure for decades. Amidst political polarization, technological transformation, and major global power shifts, Lissner and Rapp-Hooper convincingly argue, only a grand strategy of openness can protect American security and prosperity despite diminished national strength. Disciplined and forward-looking, an openness strategy would counter authoritarian competitors by preventing the emergence of closed spheres of influence, maintaining access to the global commons, supporting democracies without promoting regime change, and preserving economic interdependence. The authors provide a roadmap for the next president, who must rebuild strength at home while preparing for novel forms of international competition. Lucid, trenchant, and practical, An Open World is an essential guide to the future of geopolitics."--